2019
DOI: 10.1021/acsomega.9b02831
|View full text |Cite
|
Sign up to set email alerts
|

New Findings in the Signaling Pathways of cis and trans Platinum Iodido Complexes’ Interaction with DNA of Cancer Cells

Abstract: We have selected a series of aliphatic amine platinum compounds bearing chloride and/or iodide as the leaving groups. The complexes’ cytotoxicity and interaction with DNA indicated differences in the reactivity. Now, we are reporting on the analysis of their molecular mechanism of action on gastric cancer cells. Our data reveals differences between them. Chlorido drugs showed similar behavior to cisplatin; they both required p53 to induce apoptosis but only cis-ipa showed DNA damage requirement for apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…In particular, the N-(3bromophenyl)picolinamide substituted Ru(III) diiodido complex exhibited nanomolar potency against several cancer cell lines. Overall, the diiodido complexes were ∼13× more cytotoxic than the analogous dichlorido complexes, highlighting potentially different modes of action, similar to the Pt(II) work reported by Quiroga et al 8 Since we have already reported the potential of using picolinamide ligands to increase cytotoxicity of metal complexes, 27−29 we provide further insight into the biological cytotoxicity and the stability of the cis and trans dihalido complexes, by reporting eight new N-((3-halidophenyl)picolinamide)rhodium(III) dihalido complexes, [RhX 2 (L)-(LH)], where X = chlorido (1−4) or iodido (5−8). The complexes are fully characterized, and we report seven new crystal structures.…”
Section: ■ Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…In particular, the N-(3bromophenyl)picolinamide substituted Ru(III) diiodido complex exhibited nanomolar potency against several cancer cell lines. Overall, the diiodido complexes were ∼13× more cytotoxic than the analogous dichlorido complexes, highlighting potentially different modes of action, similar to the Pt(II) work reported by Quiroga et al 8 Since we have already reported the potential of using picolinamide ligands to increase cytotoxicity of metal complexes, 27−29 we provide further insight into the biological cytotoxicity and the stability of the cis and trans dihalido complexes, by reporting eight new N-((3-halidophenyl)picolinamide)rhodium(III) dihalido complexes, [RhX 2 (L)-(LH)], where X = chlorido (1−4) or iodido (5−8). The complexes are fully characterized, and we report seven new crystal structures.…”
Section: ■ Introductionsupporting
confidence: 81%
“…In particular, the N -(3-bromophenyl)­picolinamide substituted Ru­(III) diiodido complex exhibited nanomolar potency against several cancer cell lines. Overall, the diiodido complexes were ∼13× more cytotoxic than the analogous dichlorido complexes, highlighting potentially different modes of action, similar to the Pt­(II) work reported by Quiroga et al…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…5 In physics, platinum is employed to produce organic lightemitting diodes. 6 Platinum is broadly applied in medicine, 7,8 including various cancer and drug treatments, [9][10][11] with spectacular results. Iodine is a nonmetallic chemical element and a nonarticial stable halogen.…”
Section: Introductionmentioning
confidence: 99%